Conversations with Stanley Kunitz - Kunitz, Stanley, 1905-2006 (Literary conversations series., 2013)
""He again tops the crowd--he surpasses himself, the old iron brought to the white heat of simplicity."" That's what Robert Lowell said of the poetry of Stanley Kunitz (1905-2006) and his evolving artistry. The interviews and conversations contained in this volume derive from four decades of Kunitz's distinguished career. They touch on aesthetic motifs in his poetry, the roots of his work, his friendships in the sister arts of painting and sculpture, his interactions with Lowell and Theodore Roethke, and his comments on a host of poets: John Keats, Walt Whitman, Randall Jarrell, Wallace Steve.